2014
DOI: 10.1021/jo5005923
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Hyacinthacines B3, B4, and B5 and Purported Hyacinthacine B7, 7-epi-Hyacinthacine B7, and 7a-epi-Hyacinthacine B3 from a Common Precursor

Abstract: The total synthesis of hyacinthacines B3, B4, and B5 and purported hyacinthacine B7, 7-epi-hyacinthacine B7, and 7a-epi-hyacinthacine B3 from a common anti-1,2-amino alcohol precursor is described. These syntheses confirmed that the proposed structures and absolute configurations of hyacinthacines B3, B4, and B5 were correct and disclosed that the proposed structure of hyacinthacine B7 was incorrect. Our synthetic and spectroscopic studies suggest that the natural hyacinthacines B5 and B7 are the same compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 62 publications
3
24
0
Order By: Relevance
“…[1][2][3][4][5][6] To date, nineteen hyacinthacine alkaloids of general structure 1 (Figure. 1) have been isolated from extracts of the Hyacinthaceae family and fourteen of these hyacinthacine alkaloids have been the subject of total synthesis. [6][7][8][9][10][11][12][13][14][15] Additionally, different methods have also been employed towards the synthesis of many unnatural hyacinthacines, increasing the scope and potential finding of more potent analogues to be used as possible antiviral, anticancer, antidiabetic and anti-obesity drugs. 16,17 The current classification system for hyacinthacine alkaloids divides these compounds into the following: hyacinthacines A 1-7 , B 1-7 , and C 1-5 ; whereby the letter assignment, A, B or C, corresponds to the presence of 0, 1 or 2 hydroxy/hydroxymethyl, substituents found on the B ring, respectively (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] To date, nineteen hyacinthacine alkaloids of general structure 1 (Figure. 1) have been isolated from extracts of the Hyacinthaceae family and fourteen of these hyacinthacine alkaloids have been the subject of total synthesis. [6][7][8][9][10][11][12][13][14][15] Additionally, different methods have also been employed towards the synthesis of many unnatural hyacinthacines, increasing the scope and potential finding of more potent analogues to be used as possible antiviral, anticancer, antidiabetic and anti-obesity drugs. 16,17 The current classification system for hyacinthacine alkaloids divides these compounds into the following: hyacinthacines A 1-7 , B 1-7 , and C 1-5 ; whereby the letter assignment, A, B or C, corresponds to the presence of 0, 1 or 2 hydroxy/hydroxymethyl, substituents found on the B ring, respectively (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Hyacinthacine alkaloids have specific glycosidase inhibitory activities; they have been identified as potential anticancer, antiviral, antidiabetic, and antiobesity drugs [81].…”
Section: Resultsmentioning
confidence: 99%
“…To date, fourteen of the natural hyacinthacines, A 1 , A 2 , A 3 , A 6 , A 7 , B 1 , B 2 , B 3 , B 4 , B 5 , B 7 , C 2 , C 3 and C 5 have been synthesized, along with their related epimers and enantiomers. [51][52][53][54][55][56][57][58][59][60][61][62][63][64] At this point, the authors note that an increasing number of reports suggest the confirmation of hyacinthacine A 5 through methods of total synthesis. [61,63,65] To the best of our knowledge, hyacinthacine A 5 has not yet been synthesized and although epimers of the structure have been reported, [66] the absolute configuration of the natural isolate is still yet to be confirmed.…”
Section: Current Issues With the Hyacinthacine Alkaloidsmentioning
confidence: 99%
“…In addition to the aforementioned issues, recent synthetic studies have also revealed that the original structures proposed for hyacinthacine B 7 , C 3 and C 5 are incorrect. [58][59][60][61][62] It therefore becomes apparent that structural revision of the original isolates is necessary because as demonstrated in the earlier table, hyacinthacine alkaloid epimers determine the degree of specificity as well as the potency for the inhibition of various glycosidases.…”
Section: Current Issues With the Hyacinthacine Alkaloidsmentioning
confidence: 99%